Studies on Riceberry rice (Oryza sativa L.) extract on the key steps related to carbohydrate and lipid digestion and absorption: A new source of natural bioactive substances - Sakawrut Poosri; Thavaree Thilavech; Porntip Pasukamonset; Chaturong Suparpprom; Sirichai Adisakwattana (NFS Journal, 2019)
Riceberry rice (Oryza sativa L.), a new cross-breed from Hom Nin rice, a local non-glutinous purple rice, and Khoa Dawk Mali 105. The present study systematically assessed the effect of Riceberry rice extract (RBE) on the inhibition of key steps of carbohydrate and lipid digestion and absorption. The main anthocyanin identified in RBE was cyanidin-3-O-glucoside and peonidin-3-O-glucoside. In the step of carbohydrate digestion and absorption, RBE markedly inhibited intestinal maltase and sucrase. Kinetic analysis demonstrated that RBE was a mix-type competitive inhibitor against intestinal maltase. In Caco-2 cells, RBE had no effect on inhibition of glucose uptake but it could suppress mRNA expression of SGLT1. The results showed that RBE caused the reduction of lipid digestion and absorption by inhibiting pancreatic lipase, decreasing the micellar cholesterol solubility and binding of bile acid. Moreover, RBE showed non-competitive inhibition toward pancreatic lipase activity. In Caco-2 cells, RBE exhibited a significant reduction in cholesterol uptake and suppressed mRNA expression of NPC1L1 transporter. These findings provide important evidence that Riceberry rice may be a potential natural source for inhibiting the key steps of carbohydrate and lipid digestion and absorption. Keywords: Riceberry rice, Anthocyanin, Carbohydrate, Lipid